Application of sulfur-coated magnetic carbon nanotubes for extraction of some polycyclic aromatic hydrocarbons from water resources. (December 2022) - Sun, Wen; Hong, Yaoliang; Li, Tian; Chu, Huaqiang; Liu, Junxia; Feng, Li
Abstract: In the present work, novel sulfur-coated magnetic carbon nanotubes (MCNTs-S) material was fabricated by S coating on the MCNTs using a simple heating procedure. TGA, EDX, XRD, TEM, and VSM were employed to characterize the as-prepared composite. Using HPLC-UV system, the produced superparamagnetic sorbent was employed for the extraction and measurement of trace levels of five polycyclic aromatic hydrocarbons (PAHs) in environmental waters. The synergistic effect of the sulfur layer and CNTs substrate is primarily responsible for the remarkable extraction efficiency of the MCNTs-S sorbent towards PAHs. The experimental factors including MCNTs-S dosage, sorption time, elution solvent, ionic strength and solution pH were explored and optimized. Considering that the ionic strength and pH do not have any impact on the PAHs extraction, as a result, there is no need the unnecessary adjustment of the water samples. The linear dynamic ranges and detection limits under optimal conditions were in the range of 0.05–0.11 ng mL −1 and 0.2–150 ng mL −1, respectively. The analysis of PAHs in the real samples (sea water and river water) using this approach was successfully assessed with appropriate recovery values (94.6%–99.0%). Graphical abstract: Image 1 Highlights: The MCNTs-S sorbent represents outstanding performance for PAHs extraction from water resources. The novel MCNTs-S illustrated excellent magnetic property. The suggested MSPE technique demonstrated high sensitivity and precision.